1994
DOI: 10.1128/mcb.14.2.1395
|View full text |Cite
|
Sign up to set email alerts
|

ATBF1, a multiple-homeodomain zinc finger protein, selectively down-regulates AT-rich elements of the human alpha-fetoprotein gene.

Abstract: ATBF1 is a 306-kDa protein containing four homeodomains, 17 zinc finger motifs, and several segments potentially involved in transcriptional regulation (T. Morinaga, H. Yasuda, T. Hashimoto, K. Higashio, and T. Tamaoki, Mol. Cell. Biol. 11:6041-6049, 1991). At least one of the homeodomains of ATBF1 binds to an AT-rich element in the human a-fetoprotein (AFP) enhancer (enhancer AT motif). In the present work, we analyzed the transcriptional regulatory activity of ATBF1 with respect to the enhancer AT motif and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
66
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 26 publications
1
66
0
Order By: Relevance
“…Atbf1, which encodes AT-motif binding factor-1 protein, also was identified in our screen. Also known as "zinc-finger homeobox 3" (ZFHX3), this protein has been shown previously to negatively regulate the expression of the liver tumor marker α-fetoprotein (AFP) in hepatocytes (31). Moreover, it was demonstrated previously that ATBF1 expression was significantly reduced in 55 of 76 HCC samples (32).…”
Section: Discussionmentioning
confidence: 99%
“…Atbf1, which encodes AT-motif binding factor-1 protein, also was identified in our screen. Also known as "zinc-finger homeobox 3" (ZFHX3), this protein has been shown previously to negatively regulate the expression of the liver tumor marker α-fetoprotein (AFP) in hepatocytes (31). Moreover, it was demonstrated previously that ATBF1 expression was significantly reduced in 55 of 76 HCC samples (32).…”
Section: Discussionmentioning
confidence: 99%
“…Absence or dysfunction of the ATM protein causes ataxia-telangiectasia (AT), a human disease that shows remarkable elevation of AFP expression (Chun and Gatti, 2004). The elevation of AFP may be explained by the dysfunction of ATBF1, as ATBF1 is the major suppressive factor for Afp gene transcription (Morinaga et al, 1991;Yasuda et al, 1994). These observations suggest that the expression of ATM, a member of the PI(3)K superfamily, is highly correlated with the function of ATBF1 as a gene regulatory factor in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…ATBF1 has four homeotic domains and 23 zincfinger motifs in a single molecule that should control various target genes. Previously, the Afp (Morinaga et al, 1991;Yasuda et al, 1994) and aminopeptidase N (APN) (Kataoka et al, 2000) genes were identified as targets for ATBF1. The present study was designed based on the predicted roles for ATBF1 in neuronal differentiation both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…ATBF1 down regulates AFP gene expression in human hepatic cells through binding to the AT motif competitively with hepatocyte nuclear factor 1 (HNF1), which itself activates the transcription of AFP. 13,14 ATBF1 protein is known to interact with various proteins including c-Myb 15 and PIAS3. 16 ATBF1 represses c-Myb transcription activity through protein-protein interactions, which may in turn result in the suppression of cell growth and differentiation.…”
mentioning
confidence: 99%